Inflammaging and immunosenescence, the possible response to the severity of COVID-19 in older people. Narrative Review - Adriana Beatríz Pedreañez Santana; Jesús Alberto Mosquera Sulbarán; Nelson Enrique Muñoz Castelo (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
SARS-CoV-2 infection varies widely with age, generally being more severe in older adults. In many of these patients, a cytokine storm syndrome can be triggered, characterized by a systemic elevation of several pro-inflammatory cytokines, which could induce acute respiratory distress syndrome (ARDS), pneumonia, as well as multiple organ failure and ultimately death. During aging, the immune system can experience a gradual decline in immune function called immunosenescence, which makes it difficult to recognize, signal, and eliminate threats. A slight chronic increase in systemic inflammation called inflammatory aging, a phenomenon implicated in disorders such as diabetes mellitus, Alzheimer's and atherosclerosis, has also been described. A large body of recent data describing pathology and molecular changes in COVID-19 patients points to immunosenescence and inflammatory aging as the main drivers of high death rates in older patients. The objective of this review is to summarize the experimental data and clinical observations that link inflammaging and immunosenescence with the pathophysiology of COVID-19 in severely infected older people